1991
DOI: 10.1007/bf02935540
|View full text |Cite
|
Sign up to set email alerts
|

Role of the growth-associated protein B-50/GAP-43 in neuronal plasticity

Abstract: The neuronal phosphoprotein B-50/GAP-43 has been implicated in neuritogenesis during developmental stages of the nervous system and in regenerative processes and neuronal plasticity in the adult. The protein appears to be a member of a family of acidic substrates of protein kinase C (PKC) that bind calmodulin at low calcium concentrations. Two of these substrates, B-50 and neurogranin, share the primary sequence coding for the phospho- and calmodulin-binding sites and might exert similar functions in axonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(65 citation statements)
references
References 160 publications
1
64
0
Order By: Relevance
“…There is currently much debate on the role of B-50/GAP-43 in CNS function and particularly on its role in synaptic plasticity [5,6]. It has been proposed that in the induction phase of longterm potentiation (LTP, a cellular model for synaptic plasticity underlying learning and memory), an increased phosphorylation state of B-50/GAP-43 is observed and this increase could in turn induce an enhancement in neurotransmitter release [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently much debate on the role of B-50/GAP-43 in CNS function and particularly on its role in synaptic plasticity [5,6]. It has been proposed that in the induction phase of longterm potentiation (LTP, a cellular model for synaptic plasticity underlying learning and memory), an increased phosphorylation state of B-50/GAP-43 is observed and this increase could in turn induce an enhancement in neurotransmitter release [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The immediate early gene c-fos has, as part of its promoter, a transcription factor binding site called the cAMP response element (CRE; Ginty et al, 1994;Gispen et al, 1991). Thus, glutamate binding on NMDA receptors may activate the c-fos gene in neurons through the www.intechopen.com…”
Section: Regulation Of C-fosmentioning
confidence: 99%
“…B-50 (also known as growth-associated protein-43 (GAP-43), neuromodulin and F1; reviewed by: Liu and Storm [45]; Gispen et al [33]; Strittmatter et al [59]) is a well documented PKC substrate found predominantly in neurons at the cytosolic site of the presynaptic and the growth cone membrane, cDNA sequence analysis revealed rat B-50 as a 23.6-kDa protein of 226 amino acids with an apparent molecular weight of 43-48 kDa on SDS-PAGE. Palmitoylation of Cys-3 and/or Cys-4 of B-50 is important for its plasma membrane-association and is not required for its phosphorylation by PKC.…”
Section: B-50/gap-43mentioning
confidence: 99%